The impact of transport on the competitiveness of national economy - Mačiulis, Alminas; Vasiliauskas, Aidas V.; Jakubauskas, Gražvydas (Transport, 2009)
Transport has always been and remained one of the main driving forces in the economical development of any country including Lithuania. The paper assesses a positive impact of transport on Lithuanian economy in the light of the analysis of the main indicators measuring the success of the transport sector: the share of transport and warehousing sectors to national GDP (%) and the share of the export of transport services in GDP (%). It is also widely acknowledged that transport is going to play a crucial role in economic development in the future, especially in transit‐related transport like the Baltic States. On the other hand, the growth of transport, particularly in road transport, has had a significant impact on congestion, safety and pollution. Therefore, the task of transport decision makers is to find the key for sustainable transport development and reduction of a negative transport impact to sustain the transport sector as the engine of economy. The paper analyses both the positive and negative impacts of transport on economy and evaluates the possible ways developing the sustainable transport system. First published online: 27 Oct 2010